Equitable global health research collaborations with a mind of human dignity - Achana, Felix; Boah, Michael; Chirawurah, Dennis; Owusu-Marfo, Joseph; Ndago, Joyce Aputere; Santah, Colette; Mohammed, Abdul-Raheem; Adokiya, Martin Nyaaba (Frontiers in Education, 2023)
This paper explores the importance of equitable global health research collaborations that prioritize human dignity. It addresses the need for Global North partners to increase their efforts in raising awareness among all actors in global health. The aim is to bridge the gap in research collaborations and promote equitable practices that uphold the principles of human dignity and equity. A comprehensive review of existing literature and case studies was conducted to examine current practices and challenges in global health research collaborations. The review focused on the role of Global North partners in promoting equitable collaborations, capacity building efforts, and the impact of colonial legacies on research dynamics. The findings highlight the need for deliberate actions by Global North partners to raise awareness and promote equitable research collaborations. Initiatives such as Principal Investigator positions to partners from low- and middle-income countries (LMICs) during grant applications have been observed. Assigning first/last authorship positions to LMIC members is gaining momentum. However, further efforts are necessary to enhance the inclusivity of global health research collaborations. We emphasize the need for standardized definitions of global health that encompass human dignity and equity. Urgent action is required to ensure that all actors in global health research collaborations embrace human dignity. By deploying new techniques and tools where they are most needed, we can effectively promote equitable research collaborations that contribute to improving the health of individuals worldwide.